Assessment of Heavy Metal Contamination in Surface Water of Burullus Lagoon, Egypt - El-Alfy, Muhammad Abdul-Hady; El-Azim, Hoda Abd; El-Amier, Yasser A. (Journal of Scientific Agriculture, 2017)
Burullus Lagoon is one of the five Mediterranean Lagoons of Egypt which used for many purposes including fishing, recreation and contains many organisms. This investigation was aimed to assess the variation pattern in trace metals contamination in different sectors of Burullus Lagoon. Number of 34 representative water samples were collected and analyzed for 7 trace elements according to the standard method. Spatial distribution maps for these metals were created using ordinary Kriging method in ArcGIS. The obtained results indicated that the dissolved heavy metals in Burullus Lagoon were in the range of; Fe (10.55-48.6 µg/l), Pb (2.62-10.76 µg/l), Cu (0.80-48.21 µg/l), Zn (1.65-29.9 µg/l), Co (2.26-7.74 µg/l), Cr (nd-0.82 µg/l) and Cd (nd-9.91 µg/l). The Lagoon is receiving huge amounts of drainage water at the southern parts in comparison to the northern parts. It was also showed that, the highest mean concentrations of most dissolved trace metals take the following sequence: Western > Middle > Eastern. It is highly recommended to control the destructive human activities around the lagoon and to treat resultant wastewater before discharge into the lagoon.